Assessment of Knowledge, Attitude and Practice related to Tuberculosis among Rural and Urban Community of North India - Mittal, Vineeta; Singh, Vikramjeet; Kumar, Hemant (Indian Journal of Community Health, 2023)
Tuberculosis is known as one of the long-standing and dominating health problems affecting people and the extent further escalates in a developing country like India. A pre-evaluated feedback structured questionnaire was validated and adopted to get their quantitative data from 424 respondents. In the present study urban respondents (60.8%) gave affirmative responses regarding awareness of TB, especially with mobile media as their major source of information, followed by information from healthcare workers. Rural respondents were less expressed and deficient on knowledge of TB transmission and preventive methods. Prevention practices toward TB are claimed to be high in urban population because 79.48% believed that early diagnosis, prompt treatment and avoiding poor hygiene and crowded environment are effective strategies to cease the transmission of TB. Effective preventive and informative strategies should be employed in rural border areas to make up for the knowledge gap found among rural and urban populations in this study.